2001
DOI: 10.1200/jco.2001.19.8.2309
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Study of Rebeccamycin Analog NSC 655649 Given Daily for Five Consecutive Days

Abstract: The recommended phase II dose for NSC 665649 on a daily x 5 every 3 weeks schedule is 141 and 165 mg/m(2)/d for patients with prior and no prior therapy, respectively, with DLT being neutropenia. During this phase I trial, encouraging antitumor activity was been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…Significant interpatient variability was noted. Pharmacokinetic data from previous phase I trials showed that NSC 655649 exhibited dose-proportional kinetics over the dose range tested (11,12). Interestingly, Cl values for NSC 655649 were lower at the 550 mg/m 2 dose level in the present trial, which may explain the substantial increase in both severity and rate of toxicities at this NSC 655649 dose.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…Significant interpatient variability was noted. Pharmacokinetic data from previous phase I trials showed that NSC 655649 exhibited dose-proportional kinetics over the dose range tested (11,12). Interestingly, Cl values for NSC 655649 were lower at the 550 mg/m 2 dose level in the present trial, which may explain the substantial increase in both severity and rate of toxicities at this NSC 655649 dose.…”
Section: Discussionmentioning
confidence: 43%
“…NSC 655649 is active against cancer cells with acquired resistance to etoposide and teniposide (5). In phase I studies, NSC 655649 has shown antitumor activity in gastrointestinal tumors as well as in taxane-and platinum-resistant ovarian cancer (11,12). The enhanced clinical benefit observed with NSC 655649 in a phase II trial served in part as the impetus for an ongoing phase III trial in advanced biliary cancers (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During in vitro studies, becatecarin was shown to be active against cell lines of Ewing sarcoma, medulloblastoma, neuroblastoma and rhabdomyosarcoma, [30] and it appeared to be a more potent anticancer drug than rebeccamycin itself when tested on a leukaemia cell line. [27] A range of promising Phase I clinical trials were carried out on becatecarin between 1996 and 2002, [31][32][33][34][35][36] but in a 2008 Phase II clinical study by Langevin et al on the effects of the drug on children with solid CNS tumours, it was revealed that myelosupression was a significant side effect, [37] effectively halting the development of this drug for use on this demographic.…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%